Differences in biomechanical and EMG variables among Iraq, Iran, Turkey and Syria weightlifters during Olympic lifts - Alsoodani, A. S.; Ismaeel, S. A. (International Journal of Applied Exercise Physiology, 2012)
Weightlifting sport is one of the important sport field that get rise interesting from coaches and careers and researchers, because it's one of the Olympics event. In view of the specialist of its requirement like the fast movement and pull of the weight in fastest it's possible that for the motion analysis is needed and the main way to determine , analyses and correction the good and weak points. The aim of this study is to put a modern aspects in motion analysis field that more accuracy considering the individual differences in performance.